2021
DOI: 10.35957/jatisi.v8i1.568
|View full text |Cite
|
Sign up to set email alerts
|

Klasifikasi Topeng Cirebon menggunakan Metode Convolutional Neural Network

Abstract: Cirebon mask is one of the intangible cultural heritage in Indonesia. It is one of the prominent cultural assets from Cirebon and becoming one of the identity Cirebon culture. However, the current condition people tend to forget the cultural asset and lack of help from the government makes the Cirebon mask become the third-rate assets. Our concern lays on the extinction of this Mask. We want to implement digitation and automatic identification using image processing techniques. In this paper, we applied the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Harjoseputro, (2018) [14] classifying Javanese characters using the Convolutional Neural Network (CNN) method produces an overall accuracy rate of 85% using 1000 training images and 100 test images. Then the level of accuracy when viewed as a group of Javanese characters, it can be concluded that groups 1 and 3 with an accuracy rate of 92%, while the lowest level of accuracy when viewed per group of Javanese characters is group 2 with an accuracy rate of 72%.…”
Section: Peng Et Al (2020)mentioning
confidence: 99%
“…Harjoseputro, (2018) [14] classifying Javanese characters using the Convolutional Neural Network (CNN) method produces an overall accuracy rate of 85% using 1000 training images and 100 test images. Then the level of accuracy when viewed as a group of Javanese characters, it can be concluded that groups 1 and 3 with an accuracy rate of 92%, while the lowest level of accuracy when viewed per group of Javanese characters is group 2 with an accuracy rate of 72%.…”
Section: Peng Et Al (2020)mentioning
confidence: 99%
“…Other research using Convolutional Neural Networks for Javanese script classification obtained accuracy results of 85%. The dataset used is 20 classes of Javanese script data, each of which is contained in each folder containing 108 images [11].…”
Section: Introductionmentioning
confidence: 99%
“…The process of distinguishing between poisonous and non-poisonous mushrooms is critical for preserving ecosystems, human health, and safety [2]. Deep learning is the method approach that is most frequently implemented [1], [3].…”
Section: Introductionmentioning
confidence: 99%